Comparing Wild and Cultivated Food Plant Richness Between the Arid American and the Mesoamerican Centers of Diversity, as Means to Advance Indigenous Food Sovereignty in the Face of Climate Change - Nabhan, Gary Paul; Colunga-GarcíaMarín, Patricia; Zizumbo-Villarreal, Daniel (Frontiers in Sustainable Food Systems, 2022)
Climate change is aggravating agricultural crop failures, and the paucity of wild food harvests for Indigenous desert dwellers in Mexico and the U.S. This food production crisis challenges ongoing efforts by Indigenous communities in obtaining greater food security, prompting them to reconsider the value of traditional Indigenous food systems in both Mesoamerica and Arid America, two adjacent centers of crop diversity. While food production strategies in these two centers share many features, the food plant diversity in the Western Mesoamerican region appears to be greater. However, a higher percentage of plants in Arid America have adapted to water scarcity, heat, and damaging radiation. The phytochemical and physiological adaptations of the food plants to abiotic stresses in arid environments offer a modicum of resilience in the face of aggravated climate uncertainties. By comparing food plant genera comprising Western Mesoamerican and Arid American diets, we detected a higher ratio of CAM succulents in the wild and domesticated food plant species in the Arid American food system. We conclude that food plant diversity in the ancestral diets of both centers can provide much of the resilience needed to advance Indigenous food sovereignty and assure food security as climate change advances.